KIND‐DAMA: A modular middleware for Kinect‐like device data management. (25th August 2017) - Milazzo, Fabrizio; Gentile, Vito; Gentile, Antonio; Sorce, Salvatore
Summary: In the last decades, we have witnessed a growing interest toward touchless gestural user interfaces. Among other reasons, this is due to the large availability of different low‐cost gesture acquisition hardware (the so‐called "Kinect‐like devices"). As a consequence, there is a growing need for solutions that allow to easily integrate such devices within actual systems. In this paper, we present KIND‐DAMA, an open and modular middleware that helps in the development of interactive applications based on gestural input. We first review the existing middlewares for gestural data management. Then, we describe the proposed architecture and compare its features against the existing similar solutions we found in the literature. Finally, we present a set of studies and use cases that show the effectiveness of our proposal in some possible real‐world scenarios.